Recycled Carbonate‐Bearing Silicate Sediments in the Sources of Circum‐Mediterranean K‐Rich Lavas: Evidence From Mg‐Zn Isotopic Decoupling. Issue 3 (24th February 2023) - Shu, Zi‐Tan; Liu, Sheng‐Ao; Prelević, Dejan; Wang, Yu; Foley, Stephen F.; Cvetković, Vladica; Li, Shuguang
Abstract: The high flux of subaerial volcanic CO2 emissions around the circum‐Mediterranean region requires the involvement of an unusually carbon‐rich reservoir, but the origin of which is still unclear. Here, we aim to resolve this problem by analyzing Mg and Zn isotopes for the widely distributed mafic potassic to ultrapotassic lavas in this region. These K‐rich lavas have lower δ 26 Mg but similar δ 66 Zn compared to mid‐ocean ridge basalts (MORB). No known magmatic processes can explain the isotopic data, which must therefore be characteristics of the mantle sources. Recycled carbonate sediments are capable of explaining the low δ 26 Mg, but they typically also have high δ 66 Zn. Thus, the low δ 26 Mg but unfractionated δ 66 Zn of these K‐rich lavas define "Mg‐Zn isotopic decoupling" which has not yet been observed for other types of mantle‐derived lavas. The carbonate‐bearing silicate sediments analyzed here possess low δ 26 Mg and MORB‐like δ 66 Zn, which can account for the Mg‐Zn isotopic decoupling. Therefore, the nature of recycled materials (carbonates vs. carbonate‐bearing silicate sediments) in the mantle can be distinguished by the coupling or decoupling of Mg and Zn isotopes of mantle‐derived magmas. The input flux of carbon from the sediments to the lithospheric mantle is estimated to be ∼8.1 Mt/yr, and ∼22.4 Mt/yr of CO2 emissions are predicted, which fit well with the observed output flux of 20.1 ± 13.4 Mt/yr. Our results demonstrate that recycled crustal carbon stored in the lithospheric mantle is an important source for the extensive subaerial volcanic CO2 emissions in the circum‐Mediterranean region. Plain Language Summary: Extensive volcanic CO2 emissions around the circum‐Mediterranean region constitute a significant proportion of the global total, but the source of this carbon‐rich reservoir is unclear. We analyze Mg and Zn isotopes for the widespread, lithospheric mantle‐derived K‐rich lavas in this region and find that they have lower Mg but similar Zn isotopic data compared to mid‐ocean ridge basalts. This Mg‐Zn isotopic feature is defined as "Mg‐Zn isotopic decoupling" and explained as resulting from recycled carbonate‐bearing sediments in their mantle sources. Thus, the lithospheric mantle beneath the circum‐Mediterranean region is carbon‐rich, providing an important source for the extensive volcanic CO2 emissions. Key Points: Mg and Zn isotopic decoupling is reported for the first time in circum‐Mediterranean K‐rich lavas Carbonate‐bearing silicate sediments have been recycled into the lithospheric mantle beneath the circum‐Mediterranean region Carbon‐rich lithospheric mantle is an important source for extensive volcanic CO2 emissions